Determinants Of Islamic Financial Services Adoption In Indonesia: UTAUT-DOI Frameworks - Pratiwi, Rianti; Suwandaru, Agung; Erismen Armen, Rio; Natraza, Azrina Candra (Relevance: Journal of Management and Business, 2025)
This study examines the determinants of Islamic financial inclusion in Indonesia, focusing on internet access effects through integrated Unified Theory of Acceptance and Use of Technology (UTAUT) and Diffusion of Innovations (DOI) frameworks. Probit regression analysis was conducted on 6,606 respondents from the 2018-2019 Financial Inclusion Insights survey. The model includes internet access, demographic characteristics, and socio-economic factors, with comprehensive robustness checks including multicollinearity assessment, goodness-of-fit measures, and sensitivity analyses. Internet access is the strongest predictor of Islamic financial inclusion, with a marginal effect of 2.71 percentage points (p<0.001), representing a 160% relative increase. Marital status shows a 2.24 percentage point effect (p<0.001), while primary education contributes 0.88 percentage points (p<0.10). Unexpectedly, being male decreases adoption by 0.73 percentage points (p<0.05). Urban residence, age, higher education, and employment status show no significant effects. This research is the first to integrate UTAUT-DOI frameworks for Islamic financial services, extends UTAUT to Sharia-compliant behavior, and demonstrates that digital infrastructure can override traditional geographic barriers. The findings reveal context-dependent gender moderation and establish internet access as the highest-leverage policy intervention for expanding Islamic financial inclusion in developing countries.